The Determinants of Profit-Loss Sharing Financing of Islamic Banks in Indonesia - Kautsar Riza Salman (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2022)
Profit-loss sharing financing is one of the leading business activities carried out by Islamic banks, including buying, selling, and leasing. Thus, it is important to identify the determinants of profit-loss sharing financing of Islamic banks. This study examines the effect of capital adequacy ratios, non-performing financing, third party funds, and profit-sharing rate on mudharabah deposits of Islamic banks in Indonesia. Eleven Islamic banks in Indonesia from 2015 to 2019 periode were selected as sample of the study using purposive sampling. Data analysis using Partial Least Square with SmartPLS software version 3.3.7. The study results indicate that third-party funds have a significant positive effect on profit-loss sharing financing. The increasing number of third-party funds that Islamic banks have collected from customers impacts increasing distribution in the form of profit-loss sharing financing. The study results also indicate that the capital adequacy ratio, non-performing financing, and profit-sharing rate on mudharabah deposits do not affect profit-loss sharing financing. The implications for Islamic banks are to maintain the amount of third-party funds collection and compliance with sharia principles.